2012
DOI: 10.1108/17515631211264113
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Malaysian diaspora for cluster development initiatives

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/ authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…Studies have shown that lack of organisational support has led to dissatisfaction among IT professional returnees, which has been found among the returnees in India (Kenny et al, 2012), and the ignorance of cross-cultural adjustment among Malaysian returnees has weakened the communication process in the working environment (Talib et al, 2012). It is, therefore, clear that the concept of WA of professional returnees includes a wide spectrum of talent development and organisational support.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that lack of organisational support has led to dissatisfaction among IT professional returnees, which has been found among the returnees in India (Kenny et al, 2012), and the ignorance of cross-cultural adjustment among Malaysian returnees has weakened the communication process in the working environment (Talib et al, 2012). It is, therefore, clear that the concept of WA of professional returnees includes a wide spectrum of talent development and organisational support.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies on factors influencing returnees' WA focus mainly on cross-cultural adjustment (Talib et al, 2012), job modification (Bercovitz et al, 2013) and long-term development (Osman-Gani and Hyder, 2008), to understand the unique needs of returnees. In addition, long-term development has been found to have a direct impact on returnee's retention in the home country workplace (Osman-Gani and Hyder, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is also to be acknowledged that individuallevel migration can be driven by more than one reason. Talib et al (2012) review and study flows of diasporas and their networks, and discuss their effects on the country level through clusters and their economic consequences.…”
Section: Diaspora Flows and Reasons Behind Themmentioning
confidence: 99%
“…The shared understanding provided by diaspora resources is related to socio-cultural issues and informal institutions, but moreover, its importance in terms of communication ability and language skills has been acknowledged (for example, Brinkerhoff, 2009;Hepp et al, 2011). The multiple cultural embeddedness of diaspora involves country-related advantages (see Gillespie et al, 1999;Levitt, 2001), which may also facilitate learning and action in a third-party context, that is, have multidirectional effects (see Talib et al, 2012). vissak and Zhang (2014) illustrate how diaspora knowledge disseminates innovation via entrepreneurial activity.…”
Section: Diaspora Knowledge Abilities and Learningmentioning
confidence: 99%
See 1 more Smart Citation